Improving the use of lecture videos to increase student engagement in ESL blended learning classrooms / Nurul Amilin Razawi ... [et al.] - Razawi, Nurul Amilin; Mohamed, Nuruladilah; Abd Rahim, Mia Emily; Abd Rahim, Emma Marini (UiTM Press, 2023)
Online lecture videos in classrooms have been shown to aid learning by delivering information in a variety of formats. However, problems with learning have been discovered when lecture videos were used inappropriately and were of poor quality, potentially reducing student engagement. This study aims to investigate the students' perceptions of using lecture videos in ESL blended learning classrooms and to examine their suggestions for the lecturers to improve the use of lecture videos. The study employed mixed methods research design in which the data collection procedure and data analysis were done following two phases; quantitative and qualitative. A total of (n=146) respondents were involved in answering the questionnaire and written interview. The data gathered from the questionnaire were analysed statistically using SPSS version 28 while the data obtained from the written interview were thematically analysed using Atlas.ti. The quantitative finding showed the respondents' agreement to all items indicating their agreement that lecture videos play significant roles in ESL blended learning classrooms. The qualitative finding revealed four major enhancements suggested by the students.